2004
DOI: 10.1111/j.1365-2249.2004.02512.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte apoptosis in acute respiratory syncytial virus bronchiolitis

Abstract: SUMMARYRespiratory syncytial virus (RSV) infection may have an effect on the development of T cell memory responses. RSV bronchiolitis in infants is associated with a transient decline in circulating lymphocytes. We hypothesized that the mechanism underlying this lymphopenia is apoptosis. Blood was taken from 32 infants during primary RSV bronchiolitis and three months later. Using flow cytometry, we found that absolute numbers of both CD3+/CD4+ T-helper lymphocytes ( P = 0·029) and CD3+/CD8+ cytotoxic lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 38 publications
3
52
0
1
Order By: Relevance
“…RSV-specific T-helper cell responses, as measured by in vitro lymphoproliferation, appeared to be deficient during reinfection in infancy (12). Increased apoptosis of CD4 ϩ and CD8 ϩ lymphocytes resulting in lymphopenia also has been described for RSV-infected infants compared to uninfected controls, with the effect being greater with younger age and more severe illness (130). Mitogen-induced proliferation of peripheral blood lymphocytes in vitro was inhibited by contact with RSV-infected cell monolayers, an effect that did not prevent the expression of T-cell activation markers but impeded the cell cycle (135).…”
Section: Protective and Pathogenic Features Of The Host Responsementioning
confidence: 89%
“…RSV-specific T-helper cell responses, as measured by in vitro lymphoproliferation, appeared to be deficient during reinfection in infancy (12). Increased apoptosis of CD4 ϩ and CD8 ϩ lymphocytes resulting in lymphopenia also has been described for RSV-infected infants compared to uninfected controls, with the effect being greater with younger age and more severe illness (130). Mitogen-induced proliferation of peripheral blood lymphocytes in vitro was inhibited by contact with RSV-infected cell monolayers, an effect that did not prevent the expression of T-cell activation markers but impeded the cell cycle (135).…”
Section: Protective and Pathogenic Features Of The Host Responsementioning
confidence: 89%
“…RSV has been noted to affect a number of immune responses, including impairment of lymphoproliferation (69), decreased CD8 ϩ T cell response by human peripheral blood mononuclear cells (PBMCs) when infected in vitro (70), increased apoptosis of peripheral lymphocytes during acute infection in infants (71), increase in IL-10 and regulatory T cells in lungs of infected mice (72)(73)(74)(75), and altered dendritic cell stimulation of T cells in mice (76,77) and in human PBMCs or cord blood mononuclear cells in vitro (78)(79)(80). The G protein specifically has been associated with suppressing a number of immune responses, including induction of Toll-like receptor 3 (TLR3) or 4, IFN-␤ (81), proinflammatory responses of lung epithelial cells (82), lymphoproliferation (83), and activation of dendritic cells (84,85).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that both human and bovine strains of RSV activate apoptosis in cognate host cells at late stages of infection (4,14,30,34,37) and also sensitize the cells to extrinsic apoptotic agents (24). In mammalian cells, the AKT pathway generally promotes a prosurvival, antiapoptotic state (16,49).…”
mentioning
confidence: 99%